ANALISIS DAMPAK CURAH HUJAN DAN PERMINTAAN KONSUMEN DALAM MEMPREDIKSI TINGKAT PENJUALAN COTTON BUDS DENGAN MENGGUNAKAN METODE REGRESI LINIER BERGANDA - Mulyana Dewi, Rieke Putri; Laluma, Riffa Haviani (Universitas Sangga Buana, 2024)
This study focuses on PD. Azzahra Jaya, a company producing Cotton Buds. The goal is to develop a system that predicts maximum Cotton Buds sales using Multiple Linear Regression. The research examines the impact of rainfall and consumer demand on sales from 2019 to 2023. Data on monthly rainfall, consumer demand, and sales were analyzed. Results show rainfall negatively affects sales by -30.79%, while consumer demand has a positive impact of 82.44%. The regression model generated is Y = 0.1926 + (-0.1908)X1 + 0.9865X2, with a Standard Error of 12% and Mean Squared Error (MSE) of 1%. Practical recommendations are provided to improve production efficiency, respond to weather, and manage demand fluctuations.